Does the type of debt matter? Stock market perception in Europe - Zuzana Fungáčová; Christophe J. Godlewski; Laurent Weill (Bank of Finland, 2015)
We study the effect of bank loan and bond announcements on borrower's stock price. We apply an event study methodology on a sample of companies from 17 European countries and find that debt announcement generates a positive stock market reaction. However, our main conclusion is that the issuance of a loan exerts a significantly stronger reaction than does the issuance of a bond. This finding supports the hypothesis that loan issuance has a positive certification effect. The analysis of determinants of abnormal returns following debt announcements shows a positive impact of financial development and a negative effect of the Eurozone crisis.
URN:NBN:fi:bof-201508211366
Keywords: G14; G20; 330